Defining Autonomy in Psychiatry - Bergamin, Jessy; Luigjes, Judy; Kiverstein, Julian; Bockting, Claudi L.; Denys, Damiaan (Frontiers in Psychiatry, 2022)
Mental illness undermines a patient’s personal autonomy: the capacities of a person that enables them to live a meaningful life of their own making. So far there has been very little attention given to personal autonomy within psychiatry. This is unfortunate as personal autonomy is disturbed in different ways in psychiatric disorders, and understanding how autonomy is affected by mental illness is crucial for differential diagnosis and treatment, and also for understanding personal recovery. We will argue that disturbance of personal autonomy is related to patient’s diminished quality of life and suffering that motivates seeking treatment. We hypothesize that (1) personal autonomy is generally reduced by mental illness but (2) the effects on autonomy are expressed differently according to the underlying psychopathology, and also vary according to the (3) context, and perspective of the individual patient. We provide a discussion of how autonomy can be affected in five prototypical mental disorders; Major Depressive Disorder, Substance-use Disorders, Obsessive Compulsive Disorder, Anorexia Nervosa and Schizophrenia. We take these disorders to be illustrative of how diminished autonomy is a central but overlooked dimension of mental illness. We will use our discussion of these disorders as the basis for identifying key dimensions of autonomy that could be relevant to innovate treatment of psychiatric disorders.